Eksistensi Wasiat Wajibah sebagai Alternatif dalam Pembagian Waris yang Ahli Warisnya Beragama Non - Muslim di Indonesia - Antasiyah, Lia; Veviati, Isna; Yulianingsih, Wiwin (Universitas Sultan Ageng Tirtayasa, 2023)
The zdivision zor ztransfer zof zinheritance zrights zis zgiven zto zthe zheirs zor zif zthe zheirs zare zprevented zfrom zgetting zthe zinheritance, zthen za zwill zcan zbe zused. A zwill zis za zgift zfrom zone zperson zto zanother, zwhether zin zthe zform zof zobjects, zreceivables, zor zbenefits zto zbe zowned zby zthe zbeneficiary zas za zgift zthat ztakes zeffect zafter zthe zdeath zof zthe zperson zmaking zthe zwill. The zterm zobligatory zwill zwas zfirst zrecognized zin zthe zEgyptian zInheritance zLaw zwhich zis zused zto zhelp zmale zgrandsons zwho zare zhindered zfrom zobtaining zinheritance zdue zto zbeing zveiled zby zsons zfor zgranddaughters, zthus zwith zthe zobligatory zwill zit zallows zsomeone zwho zis zhindered zby zthe zright zto zobtain zinheritance zrights. possible zto zinherit. This research is a normative juridical research, the main material is based on several theories, concepts, and principles of law and related laws and regulations in this study. The approach used is the statute approach and the case approach. The position of non-Muslim children to the inheritance of Muslim heirs is not as heirs where in Islamic Inheritance Law does not recognize heirs to people of different religions (non-Muslims), because the purpose of inheritance itself is according to the concept of maqashid al-syariah (the purpose of inheritance Islamic law) operationally is to maintain property and offspring. This is the reason that the position of the right of non-Muslim children to the inheritance of Muslim heirs is regulated in the Islamic Inheritance Law in force in Indonesia which places children of other religions from the religion embraced by the heir not to inherit but to obtain a mandatory will.